Comparison of Intramedullary Pin Tie-In Configuration and Type Ia ESF With Double Connecting Bars for Tibial and Humeral Fractures in Dogs - A Dongre, Nakul; Balappanavar, B R; N, Nagaraju; , Manjunatha; N M, Rajashailesha; V, Shivakumar; V, Aswathanarayanappa (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The current study of intramedullary pin Tie-in configuration (Group I) and Type Ia ESF with double connecting bars (Group II) were  evaluated for repair of tibial and humeral fractures in dogs. The study was conducted in 12 dogs divided into two groups of six each  evaluated for 60 days. Lameness grading done on the post-operative day 1st, 15th, 30th and 60th showed a gradual decrease in lameness  score and progressed to barely noticeable to no lameness on the 60th day. Orthogonal radiographs taken on the 15th post-operative  day revealed callus formation in the majority of the cases in both groups. On the 60th post-operative day, orthogonal radiographs  revealed cortical continuity in the majority of the cases. Complete removal of the fixator was around 70 days. Two cases in Group II had  major complications. All the dogs recovered uneventfully in Group I. The intramedullary pin in Tie-in configuration as well as a second  connecting bar both increased the stiffness of Type Ia ESF.
Keywords: Canine; Humerus; IMP Tie-in; Long bone; Tibia; Type Ia ESF.